2014
DOI: 10.1111/bre.12082
|View full text |Cite
|
Sign up to set email alerts
|

Non‐unique stratal geometries: implications for sequence stratigraphic interpretations

Abstract: There is now strong evidence that stratal geometries on basin margins are most likely a consequence of multiple controls, not just variations in accommodation. Consequently, correct sequence stratigraphic interpretation of stratal geometries requires an understanding of how multiple different controls may generate similar geometries. Using a simple numerical stratigraphic forward model, we explore the impact of time variable sediment supply and different sediment transport rates on stratal geometries. We demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
105
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(118 citation statements)
references
References 57 publications
4
105
0
2
Order By: Relevance
“…many parameters) and multi-modal (i.e. non-unique solutions) forward model where numerous combinations of interacting parameters could potentially produce identical sequences (Burgess et al, 2006;Burgess and Prince, 2015). Given a specific reef core dataset and pyReef-Core, the task of finding the model parameter space that best describes the reef core data can be defined as the inverse modelling problem (Jessell, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…many parameters) and multi-modal (i.e. non-unique solutions) forward model where numerous combinations of interacting parameters could potentially produce identical sequences (Burgess et al, 2006;Burgess and Prince, 2015). Given a specific reef core dataset and pyReef-Core, the task of finding the model parameter space that best describes the reef core data can be defined as the inverse modelling problem (Jessell, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…However, SFM has become a popular heuristic tool to better understand and quantify parameters regulating peritidal carbonates (Burgess and Prince, 2015), the development of coral reef environments (Bosscher and Southam, 1992;Clavera-Gispert et al, 2017) as well as microbial (Parcell, 2003) and coral reef growth (Paulay and McEdward, 1990;Bosscher and Southam, 1992;Dalmasso et al, 2001). Early forward models were 1-D (Schwarzacher, 1966) or 2-D in formulation (Bosence and Waltham, 1990;Kendall et al, 1991), but improvements in computing led to the development of more complex, 3-D models (e.g.…”
Section: Sfm Of Carbonate Systemsmentioning
confidence: 99%
“…This conceptual knowledge is very useful to obtain consistent interpretations, but it may also, if inappropriate, be a source of errors in the correlations and in further analysis. In the forward sense, it has also been shown that several depositional scenarios can produce the same succession of stratigraphic units (Helland-Hansen and Gjelberg, 1994;Armitage et al, 2015;Burgess and Prince, 2015), which motivates the consideration of multiple correlation hypotheses. Even under the same set of hypotheses, correlation lines can be uncertain and are not easily formulated in a systematic and repeatable way when drawn manually by experts (Borgomano et al, 2008;Koehrer et al, 2011;Colombera et al, 2012;Lallier et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, SFM has become a popular heuristic tool to better understand and quantify parameters regulating peritidal carbonates (Burgess and Prince, 2015), the development of factors affecting growth have been classified by Veron (2011) as latitude-correlated factors, and those that are regional or local in character. Latitude-correlated factors include sea surface temperatures (SSTs), solar radiation and water chemistry (Kleypas et al, 1999).…”
mentioning
confidence: 99%
“…many parameters) and multi-modal (i.e. non-unique solutions) forward model where numerous combinations of interacting parameters could potentially produce identical sequences (Burgess et al, 2006;Burgess and Prince, 2015). Given a specific reef core dataset and pyReef-Core, the task of finding the model parameters space that best describes the reef core data can be defined as the inverse modelling problem (Jessell, 2002 (Andrieu et al, 2003).…”
mentioning
confidence: 99%